Empirical Analysis of Factors Promoting Product Innovation in ASEAN Economies: Focusing on Absorptive Capacity and ICT Use - Hiroki Idota; Teruyuki Bunno; Yasushi Ueki; Sobee Shinohara (International Telecommunications Society (ITS), 2015)
In recent years, East Asian economies have been rapidly developing. The reason is that firms have been successfully achieving product and process innovation by introducing advanced technologies and know-how from MNCs. In order to enhance innovation, firms have to own technology, capability and ICT use. In particular, collaborations with outside organizations such as MNCs (Multi-national corporations), universities, public organizations, local firms are indispensable for firms in developing economies. Authors' previous research clarified external linkages enhance innovation capability and ICT use, and innovation capability and ICT use promote product innovation in ASEAN firms. These studies analyzed under what conditions firms can promote absorptive capability if they had external linkages. Whether or how absorptive capacity affected innovation capability and ICT use were not explained there. Based on survey data from four ASEAN economies such as Indonesia, the Philippines, Thailand, and Vietnam, from 2013 to 2014, this study clarifies how absorptive capacity, ICTs, and innovation capability such as QC and cross-functional team enhance product innovation by using SEM (Structural equation modeling). As a result, the following causality from external linkages (origin) to innovation (final outcome) is demonstrated: (i) absorptive capacity is enhanced by external linkages such as local firms, public organizations, and universities; (ii) absorptive capacity enhances innovation capability; (iii) innovation capability enhances ICT use; and (iv) innovation capability and ICT use promote product innovation. These are similar to those of authors' previous research. Since data are different, it is difficult to compare the results, but the robustness of the results is demonstrated.
Keywords: 330; ICT use; absorptive capacity; external linkages; product innovation; SEM (Structural equation modeling)